Changes in serotype distribution and antimicrobial nonsusceptibility of Streptococcus pneumoniae among hospitalized children: Shenzhen, China, 2009–2019 - Feiling Wang; Xiaojing Zeng; Qianqian Du; Yingqi Deng; Jing Peng; Rui Dong; Wenyan Hu; Hongbo Xie; Wei Shi; Haitao Chen; Ping Jin; Kaihu Yao; et al. (Expert Review of Vaccines, 2025)
Background This study assessed changes in Streptococcus pneumoniae serotype distribution and antimicrobial nonsusceptibility among hospitalized children with pneumonia in Shenzhen, China, from 2009 to 2019, under low pneumococcal conjugate vaccine (PCV) coverage.Research Design and Methods We analyzed 1,361 isolates (62 invasive, 1,299 noninvasive). Serotypes were identified by latex agglutination and Quellung reaction. Antimicrobial susceptibility was determined using E-test, and vaccination data were obtained from the local CDC.Results PCV13 serotype coverage remained high among invasive isolates (96.8%) and represented a substantial proportion of all isolates. A marked decline in serotype 19F (from 59.2% to 14.4%) and increased serotype diversity (from 14 to 26 types) were observed. Non-susceptible rates to four beta-lactam antibiotics decreased from 16.0% to 2.4%, largely due to the decline of serotype 19F. PCV vaccination rates rose to 31.1% by 2019. Non-vaccine serotypes increased over time, with some (e.g. 15B/C) showing elevated beta-lactam MICs.Conclusions Despite low vaccination rate, PCV13 serotypes remained predominant among isolates. The decline of serotype 19F and reduced beta-lactam nonsusceptibility suggest vaccine impact. Rising serotype diversity and the emergence of nonsusceptible non-vaccine types highlight the need for continued surveillance.